2001
DOI: 10.1063/1.1397310
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical and theoretical studies of naphthalene-substituted oligothiophenes

Abstract: A comprehensive photophysical characterization of a new class of naphthalene derivatives of the important α-oligothiophenes (αn’s) has been undertaken in solution at room (293 K) and low (77 K) temperature. This includes absorption and fluorescence spectra, fluorescence quantum yields (φF), and lifetimes (τF), as a function of temperature and solvent. Triplet–triplet absorption spectra and triplet formation quantum yields (φT) were also determined. From the above, all the rate constants for the radiative (kF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
89
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(110 citation statements)
references
References 23 publications
19
89
2
Order By: Relevance
“…In the case of EHOPV3P and HPV3P, where virtually no change in the / F value is observed upon going to 77 K this was attributed to the fact that the S 1 state probably has the same geometry as that found at RT [7]. The decrease of the / F values upon lowering the temperature contrasts with the behaviour found for thiophene oligomers where an increase or constancy of this value was observed [20,23]. Thus the marked change (either increase or decrease) in the / F values upon going to LT can be associated with induced conformational changes, which is also in agreement with the marked redshift of the absorption and emission spectra when compared to the RT data.…”
Section: Solution and Solid-state Photophysical Behaviourmentioning
confidence: 84%
See 1 more Smart Citation
“…In the case of EHOPV3P and HPV3P, where virtually no change in the / F value is observed upon going to 77 K this was attributed to the fact that the S 1 state probably has the same geometry as that found at RT [7]. The decrease of the / F values upon lowering the temperature contrasts with the behaviour found for thiophene oligomers where an increase or constancy of this value was observed [20,23]. Thus the marked change (either increase or decrease) in the / F values upon going to LT can be associated with induced conformational changes, which is also in agreement with the marked redshift of the absorption and emission spectra when compared to the RT data.…”
Section: Solution and Solid-state Photophysical Behaviourmentioning
confidence: 84%
“…The / T values were obtained by comparing the DOD at 525 nm of a benzene solution of benzophenone (the standard) and of the compound (optically matched at the laser wavelength) using the equation [23,24]:…”
Section: Spectroscopic Measurementsmentioning
confidence: 99%
“…The optical properties of polymers P1-P4 were examined, [74][75][76][77] and the data are summarized in Table 2. Figure 4a shows their UV-vis absorption spectra in CHCl 3 (1.0Â10 À5 M).…”
Section: Oligothiophene-stacked Polymers Y Morisaki Et Almentioning
confidence: 99%
“…64 It is suggested that this absorption band is assigned to the S 0 -S 1 transition of the bithiophene-naphthalene moiety and the S 1 state adopts a quinoidal-like structure of thiophene with naphthalene. 75,76 The bithiophenes in P1 as well as oligothiophenes in P2-P4 have difficulty in rotating freely because of the hexyl Figure 3 Matrix-assisted laser desorption ionization time-of-flight mass spectrum of polymer P1 using all-trans-retinoic acid as a matrix.…”
Section: Oligothiophene-stacked Polymers Y Morisaki Et Almentioning
confidence: 99%
“…33 Triplet-singlet difference absorption spectra and yields were obtained using an Applied Photophysics laser flash photolysis equipment pumped by a Nd:YAG laser (Spectra Physics) with excitation wavelengths of 355 nm (leuco forms) and 535 nm (keto forms) as described elsewhere. 34 First-order kinetics was observed for the decay of the lowest triplet state. The transient spectra (300-700 nm) were obtained by monitoring the optical density change at 5-10 nm intervals, averaging at least 10 decays at each wavelength.…”
Section: Methodsmentioning
confidence: 99%